Simultaneous Determination of Thickness and Heat Conductivity in Fabric Design: Steady-state Modeling and PSO Algorithms (Journal of Fiber Bioengineering and Informatics, 2013)
Fabric thickness and texture directly affect heat and moisture transfer characteristics in the humanbody-fabric-environment system, which determine the heat-moisture comfort level of the human body.Based on the model of steady-state heat and moisture transfer from skin to environment, we putforward an Inverse Problem of Thickness-texture Determination (IPTTD). Adopting the idea of theleast-squares method, we formulate IPTTD into a function minimization problem. We employ ParticleSwarm Optimization (PSO) method to directly search optimal solution of the objective function. Theresults of numerical simulation show the effectiveness of the presented algorithms and validity of theproposed IPTTD.